2020
DOI: 10.3389/feduc.2020.578389
|View full text |Cite
|
Sign up to set email alerts
|

Assistive Technology to Promote Communication and Social Interaction for People With Deafblindness: A Systematic Review

Abstract: Background: People with deafblindness experience stigmatization, exclusion, and isolation. Due to complex communication challenges, feelings of isolation and exclusion can increase. However, assistive technology can change these negative outcomes. The aim of this systematic review is to synthesize and analyze the research published in journal articles focused on the use of assistive technology to improve communication and social interaction for people with deafblindness. Methods: A qualitative review study, ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
(163 reference statements)
0
12
0
1
Order By: Relevance
“…Similarly, previous studies have shown that AT can positively affect the lives and independence of people with ID and promote the rights of inclusion and choice for this group [9][10][11]24]. AT can also improve interaction and communication with other people, essential for emotional and social well-being; without access to AT, people with ID can be excluded and left behind [37,38]. Interestingly, dignity was a highlighted aspect of independence and coping, and the staff believed that AT should be used in a conscious way to ensure the dignity of people with ID.…”
Section: Discussionmentioning
confidence: 86%
“…Similarly, previous studies have shown that AT can positively affect the lives and independence of people with ID and promote the rights of inclusion and choice for this group [9][10][11]24]. AT can also improve interaction and communication with other people, essential for emotional and social well-being; without access to AT, people with ID can be excluded and left behind [37,38]. Interestingly, dignity was a highlighted aspect of independence and coping, and the staff believed that AT should be used in a conscious way to ensure the dignity of people with ID.…”
Section: Discussionmentioning
confidence: 86%
“…People with intellectual disabilities increasingly use the internet, but may experience more barriers with using it than people without intellectual disabilities (Chadwick et al, 2013 ). On the other hand, the use of ICT may positively impact the well‐being of people with intellectual disabilities (e.g., Caton & Chapman, 2016 ; Den Brok & Sterkenburg, 2015 ; Dyzel et al, 2020 ; Oudshoorn et al, 2020 ). The aim of this systematic review was to gain insight into the available scientific evidence on the use and feasibility of virtual social contact by people with intellectual disabilities living in home care facilities, and the potential to mitigate the impact of restricted in‐person visiting policies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,Dyzel et al (2020) pointed at the need for more research on the usability of assistive technologies for people with deafblindness, including user experiences. Our findings emphasise that more research on the use of specialised technology for facilitating virtual social contact is needed for the broader population of people with intellectual and multiple disabilities.…”
mentioning
confidence: 99%
“… 28 In the case of deafblindness, the lack of engagement of the community in participatory research reveals a systemic barrier. 29 The development and implementation of innovative technology solutions has been identified as a priority in deafblindness by stakeholders 5 ; however, its design frequently does not include device users, 30 31 with few exceptions. 32 33 This is likely because research involving this population is possible but can be challenging.…”
Section: Participatory Action Approach To Removing Barriersmentioning
confidence: 99%